CRP LEVEL WITH THE SEVERITY OF COVID-19 PATIENTS AT GOTONG ROYONG HOSPITAL SURABAYA - Christopher Christopher; Mulya Dinata; Yudita Wulandari (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). C-Reactive Protein (CRP) is an inflammatory protein that is synthesized in the liver and produced in response to inflammation. Several studies have shown a relationship between CRP levels and the severity of COVID-19.Objective: This study aims to analyze the relationship between CRP levels and the severity of COVID-19 at Gotong Royong Hospital Surabaya.Methods: This study used a cross-sectional design. Data collected through medical records from COVID-19 patients who were hospitalized at Gotong Royong Hospital Surabaya from July to December 2021.Results: There are 82 samples were collected in this study. Based on statistical analysis test, there is a significant relationship between CRP level and severity of COVID-19 with p = 0.000. The value of correlation coefficient is 0.660 which is indicating a positive correlation with a strong relationship between CRP levels and the severity of COVID-19. A high CRP level indicates a wider inflammation in the body, which is related to the severity of COVID-19.Conclusion: There is a significant relationship between CRP levels and the severity of COVID-19